Networking basics project manual - Miller, Frank 1956- (Wiley pathways, 2007)
Networks have become the life's blood of most organizations and have even found a place in a rapidly growing number of homes. This book introduces network concepts from the underlying standards, through local and wide-area network configurations, up to configurations found in today's massive enterprise networks.